EFL Learners’ Perceptions of Small Group Discussion Technique for Building Speaking Confidence in Non-Formal Education - Syadzilia Aluv Mawsally; Sri Wuli Fitriati; Yuliati Yuliati (Journal of English Language and Education, 2026)
Speaking in English remains challenging for many EFL learners because oral performance requires confidence. Small group discussion (SGD) is one activity used in EFL speaking instruction. Previous studies have examined SGD from various perspectives in EFL learning. However, the role of SGD in supporting students’ speaking confidence before oral performance in non-formal EFL settings remains underexplored, especially the aspects of confidence supported by SGD and the discussion features that contribute to students’ confidence. This study investigated EFL students’ perceptions of SGD in supporting speaking confidence before oral performance. Using a qualitative descriptive design, this study involved seventh-grade EFL learners at a non-formal English course institution in Central Java. Data were collected through classroom observation, a screening questionnaire, and semi-structured interviews. The data were analyzed using thematic analysis. The findings showed that students perceived SGD as a structured preparatory activity that helped them understand the material, exchange ideas, rehearse speaking parts, and organize ideas before oral performance. SGD also supported students’ confidence through peer support, respectful responses, clear role distribution, equal speaking opportunities, and manageable group size. These findings suggest that SGD serves as a preparatory activity in EFL speaking instruction to encourage participation and help students approach oral performance with greater confidence.